THE PHILOSOPHY OF THE «OMOTENASHI» CONCEPT IN THE INTERNATIONAL HOTEL AND RESTAURANT INDUSTRY (Development Service Industry Management, 2025)
The article examines the philosophical and practical aspects of the concept of ««omotenashi» » in the international hotel and restaurant industry. «Оmotenashi», being a unique Japanese model of hospitality, goes beyond standard service and is a deep philosophy of care, sincerity and attentive attitude to each guest. The main difference of this approach is its selflessness and the desire to anticipate the expectations of visitors, creating for them not just comfortable conditions, but an unforgettable emotional experience.The historical roots of «omotenashi»  are considered, which go back to the traditions of the Japanese tea ceremony, where each element of service has a deep meaning and symbolizes respect for the guest. It is emphasized that this principle goes beyond the hospitality industry and is widely used in Japanese society, including the sphere of business, retail and customer service. The article analyzes how this concept is adapted in various international hotels and restaurants, in particular in the premium and luxury segments, where a high level of personalized service plays a key role.Important attention is paid to comparing the Western model of service, focused on transactional relationships with customers, and «omotenashi», which is based on a sincere desire to provide the best possible experience without expecting immediate benefits. The main elements that make up «omotenashi»  are analyzed: anticipating customer needs, attention to detail, unobtrusiveness, creating an atmosphere of harmony and trust. It is noted that this approach contributes to increasing customer loyalty, strengthening the company's image and creating a unique competitive advantage.The impact of «omotenashi»  on modern trends in the hotel and restaurant industry is also considered, including the use of digital technologies for personalization of service, the introduction of innovative solutions in service and the development of the concept of «invisible service», where customer care occurs naturally and imperceptibly. It is emphasized that the integration of «omotenashi»  into international practice requires adaptation taking into account the cultural characteristics of different regions, but at the same time remains an effective tool for creating a unique customer experience.In conclusion, it is emphasized that further study of the «omotenashi»  philosophy and its application in the global hospitality industry can contribute to the formation of new service standards based on sincerity, attention and deep respect for each guest. In conditions of high competition in the hotel and restaurant services market, the introduction of «omotenashi»  principles becomes an important strategic tool that will contribute not only to improving the quality of service, but also to creating an emotional connection between the brand and customers.
Keywords: «omotenashi»; concept; hospitality; philosophy; hotel and restaurant business; international hotel and restaurant industry